2020
DOI: 10.1111/sum.12575
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced‐efficiency nitrogen fertilizers reduce winter losses of nitrous oxide, but not of ammonia, from no‐till soil in a subtropical agroecosystem

Abstract: Nitrogen (N) gas losses can be reduced by using enhanced‐efficiency N (EEN) fertilizers such as urease inhibitors and coating technologies. In this work, we assessed the potential of EEN fertilizers to reduce winter losses of nitrous oxide (N2O‐N) and ammonia (NH3‐N) from a subtropical field experiment on a clayey Inceptisol under no‐till in Southern Brazil. The EEN sources used included urea containing N‐(n‐butyl) thiophosphoric triamide (UR+NBPT), polymer‐coated urea (P‐CU) and copper‐and‐boron‐coated urea (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…It is known that soil moisture influences the peak and duration of NH 3 -N volatilization. Ribeiro et al (2020) observed that N losses from amide fertilizers, including conventional urea and NBPT-treated urea, occurred 10 days after application and were associated with increased soil temperature and moisture.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is known that soil moisture influences the peak and duration of NH 3 -N volatilization. Ribeiro et al (2020) observed that N losses from amide fertilizers, including conventional urea and NBPT-treated urea, occurred 10 days after application and were associated with increased soil temperature and moisture.…”
Section: Discussionmentioning
confidence: 99%
“…With a delay in initial N loss, there is a greater chance for granules to be incorporated into the soil, through rainfall, for instance, reducing NH 3 -N volatilization. Dall'Orsoletta et al (2017) and Ribeiro et al (2020) observed that NBPT was effective in reducing soil NH 4 + levels in the first days after application compared with conventional urea. In the current study, we found that at 45 kg ha -1 of N, Ur-NBPT delayed the volatilization peak by one day compared with Ur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a climate mitigation perspective, it is imperative to reduce N 2 O emissions by lowering N input to soil, or fine tuning the N cycling process to completely oxidize ammonia to nitrate without producing N 2 O as a by‐product (Jansson & Hofmockel, 2020). Researchers are developing a variety of strategies, for example urease inhibiting and coating technologies have been tried to reduce soil N 2 O emission, with varying levels of success (Ribeiro et al., 2020).…”
Section: Soil Management and Greenhouse Gas Emissionmentioning
confidence: 99%
“…Conventional urea is the most common N source used by maize farmers worldwide (Heffer & Prud'homme, 2016). The popularity of conventional urea can be explained by its high N content (44-46%), low cost, and ease of application (Ribeiro et al, 2020). On the other hand, its greatest disadvantage is the high susceptibility to ammonia (NH 3 ) volatilization.…”
Section: Introductionmentioning
confidence: 99%